2021
DOI: 10.18805/ijar.b-4225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Janova, Sepia and Ovsynch Protocol on Blood Biochemical Profile and Fertility in Postpartum Anoestrus Cows

Abstract: Background: Anoestrus is still one of the most prevalent reproductive disorders in dairy cows despite technological advances in animal husbandry. Evaluation of blood biochemical profile is of diagnostic value to determine disease or health status of animal. The current study was aimed to evaluate the effect of different therapeutic regimen on blood biochemical profile, oestrus induction response and conception rate of anoestrus cows.Methods: Thirty two postpartum anoestrus cows randomly allocated to four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Our results indicate similar estrus induction rate, whereas lower conception rate. The lower conception rate in our study might be due to first service conception rate against three service (AI) conception rate parameter used by Kumar et al (2021). In earlier studies different herbal seeds, preparations and combinations were tried and reported 50 to 87% estrus indication response in bovines (Despande et al, 2000;Pugashetti et al 2009;Srivastava et al, 2003;Sahatpure et al, 2016).…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Our results indicate similar estrus induction rate, whereas lower conception rate. The lower conception rate in our study might be due to first service conception rate against three service (AI) conception rate parameter used by Kumar et al (2021). In earlier studies different herbal seeds, preparations and combinations were tried and reported 50 to 87% estrus indication response in bovines (Despande et al, 2000;Pugashetti et al 2009;Srivastava et al, 2003;Sahatpure et al, 2016).…”
Section: Resultsmentioning
confidence: 68%
“…Moreover, estrus response was observed within 15 days in 83% (15/18) animals, while 17% (3/18) animals showed estrus within 19 to 23 days after treatment. Kumar et al (2021) observed that polyherbal preparation with mineral mix could induce estrus with higher conception rate than the hormonal treatment alone in anestrous cows and reported 60% estrus induction and 80% conception rates. Our results indicate similar estrus induction rate, whereas lower conception rate.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Hormonal interventions have been developed to control ovarian dynamics and allow the use of AI without heat detection. & Fahmy, 2007;Atabay et al, 2019;Bartolomeu et al, 2002;Berber et al, 2001;Campanile et al, 2005;De Araujo Berber et al, 2002;Derar et al, 2012;Francillo et al, 2005;Hoque et al, 2014;Liang et al, 2007;Neglia et al, 2003;Presicce et al, 2004;Ravikumar et al, 2009;Sathiamoorthy et al, 2007;Sianturi et al, 2012 Ovsynch + FTAI 12 and 24 h after 2nd GnRH -18.0-59 Akhtar et al, 2013;Camelo et al, 2002;Chaikhun, Tharasanit, & Rattanatep, 2010;Karen & Darwish, 2010 Presynch…”
Section: Ovulation Synchronization (Ovsynch) and Fixed Time Artificia...mentioning
confidence: 99%